PENILAIAN INDEK E-GOVERMENT PADA DINKES KOTA PALEMBANG - Fery Antony; Rendra Gustriansyah; Ryan Ramanda Putra (UNIVERSITAS INDO GLOBAL MANDIRI)
Ranking of e-Government of Indonesia (PEGI) is a model developed by the Directorate of e-Government, the Directorate General of Telematics Applications, Ministry of Communication and Information Technology (Ministry KOMINFO) to view a map of the condition of usage of Information Technology dam Communication Technologies (ICT) by government agencies nationwide , In this paper, the authors have assessed the use of ICT in the health office (DHO) of the city of Palembang as a government agency in order to facilitate the flow of information and improve the quality of service to the community by using a model approach PEGI. Palembang city health office has e-government index amounted to 1,426, which means the use of ICT in dinkes indkator Palembang city already exists, but is still lacking in terms of quantity and quality. Recommendations are given to dinkes Palembang to increase the index of e-governement it was the preparation of the Master Plan for Information Technology (RITI), preparation of the scale of the policy priorities of ICT implementation, increasing the number of staff in the section on data and health information with a background in IT, the addition of human resources development program with sending employees on section data and health information for training or education in the field of IT and Disaster Recovery planning.